2021
DOI: 10.3389/fanim.2021.712919
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Benefit of Bulls Being Fed Moringa Leaves Twigs and Branches as a Major Concentrate Ingredient

Abstract: The study was conducted to investigate nutrient metabolism and semen quality of bulls fed with moringa (Moringa oleifera) leaves, twigs, and branches as a major concentrate ingredient. Twenty-one Red Chittagong bulls of about 204 (±50) kg initial live weight (LW) were randomly divided into three equal LW groups. They were fed maize silage as a basal feedstuff for 65 days with the supplementation of concentrate mixtures at 1% of LW, consisting of either 0, 25, or 50% moringa mash on a fresh basis. Moringa mash … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…ML feed decreased enteric methane emission and increased milk production in dairy cows as reported by Bashar et al ( 2020 ). ML feeding may reduce the energy loss including methane and urinary nitrogen without having an effect on beef cattle production (Sultana et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…ML feed decreased enteric methane emission and increased milk production in dairy cows as reported by Bashar et al ( 2020 ). ML feeding may reduce the energy loss including methane and urinary nitrogen without having an effect on beef cattle production (Sultana et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Kekana et al (2022) showed that supplementation with M. oleifera leaf meal at 16.6 g/100 kg body weight had no effect on the dry matter intake and body weight of cows, calf birth weight, or colostrum yield. In another experiment, the replacement of conventional concentrate ingredients (particularly ground corn, soybean meal, and wheat bran) with up to 50% mixtures of Moringa mash (leaves, twigs, and branches of Moringa) did not affect the DM intake or live weight gain of bulls (Sultana et al, 2021). The body weight, weight gain, and height at withers of crossbred calves fed TMR without and with 5% DM of M. oleifera meal were not affected (Sherasiya et al, 2022).…”
Section: Use In Cattle Feedingmentioning
confidence: 96%
“…Moreover, rumen methanogenesis could be inhibited by phenols and tannins, resulting in inhibition of rumen CH 4 production, as reflected in the improved fat yield and efficiency of milk production (Shaani et al, 2016;Dong et al, 2019). In addition, Moringa foliage is a good source of protein and amino acids, which can enhance the utilization of dietary N (Figure 2), boosting the productivity of dairy and beef cattle (Bashar et al, 2020;Sultana et al, 2021).…”
Section: Use In Cattle Feedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have been done in dairy cattle incorporating moringa leaves in feed at different levels of inclusion. Sultana et al (2021) reported no significant difference in digestibility of nutrients of Red Chittagong bulls fed with moringa leaves and twigs in concentrate mixture at 0, 25 and 50 per cent. In buffaloes, studies related to concentrate feed incorporating dried moringa leaves are minimal.…”
Section: Introductionmentioning
confidence: 92%